2022
DOI: 10.3390/antiox11061121
|View full text |Cite
|
Sign up to set email alerts
|

Focus on the Contribution of Oxidative Stress in Skin Aging

Abstract: Skin aging is one of the most evident signs of human aging. Modification of the skin during the life span is characterized by fine lines and wrinkling, loss of elasticity and volume, laxity, rough-textured appearance, and pallor. In contrast, photoaged skin is associated with uneven pigmentation (age spot) and is markedly wrinkled. At the cellular and molecular level, it consists of multiple interconnected processes based on biochemical reactions, genetic programs, and occurrence of external stimulation. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 388 publications
0
63
0
2
Order By: Relevance
“…Regarding mechanisms accounting for photoaging, UV irradiation is known to generate reactive oxygen species (ROS), leading to marked oxidative stress, which impairs the skin functional and regenerative potential. Moreover, activation of photoaging triggers cellular senescence and inflammation, a condition known as inflammaging, and progressively suppresses the skin immune system, increasing susceptibility to infection, degenerative processes, and cancer [ 42 , 43 ]. Molecular targets, including epidermal growth factor (EGF), keratinocyte growth factor, tumor necrosis factor (TNF)-α, and interleukin (IL)-1, are activated by UV radiation, thus, stimulating the transcription factor AP-1, which blocks the synthesis of collagen, while promoting transcription of matrix metalloproteinase (MMP) genes, which in turn triggers imperfect tissue repair and dermal damage [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding mechanisms accounting for photoaging, UV irradiation is known to generate reactive oxygen species (ROS), leading to marked oxidative stress, which impairs the skin functional and regenerative potential. Moreover, activation of photoaging triggers cellular senescence and inflammation, a condition known as inflammaging, and progressively suppresses the skin immune system, increasing susceptibility to infection, degenerative processes, and cancer [ 42 , 43 ]. Molecular targets, including epidermal growth factor (EGF), keratinocyte growth factor, tumor necrosis factor (TNF)-α, and interleukin (IL)-1, are activated by UV radiation, thus, stimulating the transcription factor AP-1, which blocks the synthesis of collagen, while promoting transcription of matrix metalloproteinase (MMP) genes, which in turn triggers imperfect tissue repair and dermal damage [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have observed that PLR treatment (topical application) of mice with UVB-induced photoaging led to increased skin expression of BMAL1 (an aging suppressor) and major antioxidant enzymes, as well as a decreased ROS level. The literature has established that ROS plays a critical role in skin damage and aging caused by UV radiation ( Papaccio et al, 2022 ). UV-generated ROS leads to oxidative stress in the skin and thus to various cellular changes such as an increase in MMPs expression, enhanced collagen degradation and impaired collagen synthesis, which reflect major aspects of skin aging ( Kim et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiologies of premature skin aging (or photoaging) are not fully elucidated, several contributing factors have been identified, including oxidative stress [i.e., formation of reactive oxygen species (ROS)], mutations of mitochondrial DNA, and shortening of telomeres ( Beani, 2014 ; Papaccio et al, 2022 ; Son et al, 2022 ). Notably, ROS exerts a critical role in photoaging.…”
Section: Introductionmentioning
confidence: 99%
“…As recently reviewed by Bernerd et al [ 37 ] and Papaccio et al [ 58 ], chronic UV exposure promotes protein oxidation and carbonylation in the epidermis and dermis, and the accumulation of oxidatively modified and damaged proteins. RCS-adducts are detected in human skin biopsies, in keratinocytes, fibroblasts [ 59 , 60 ] and ECM [ 61 ].…”
Section: Post-translational Modifications Of Dermis Components By Rcsmentioning
confidence: 99%
“…ECM components (collagen, elastin, glycosaminoglycans), are primary targets of oxidative and carbonyl attack during photoaging [ 58 ]. Zucchi et al recently reported that carbonylated proteins are formed on the connective tissue in the dermis from sun-exposed human skin, specifically MDA-adduct deposits, which may accumulate on collagen [ 44 ].…”
Section: Post-translational Modifications Of Dermis Components By Rcsmentioning
confidence: 99%